Patient-reported improvements in paroxysmal nocturnal hemoglobinuria treated with iptacopan from 2 phase 3 studies - Antonio M. Risitano; Carlos de Castro; Bing Han; Austin Kulasekararaj; Jaroslaw P. Maciejewski; Phillip Scheinberg; Yasutaka Ueda; Susan Vallow; Georgina Bermann; Marion Dahlke; Rakesh Kumar; Régis Peffault de Latour (Blood Advances)
Abstract: Iptacopan, a first-in-class, oral, selective complement factor B inhibitor, demonstrated efficacy and safety as monotherapy in C5 inhibitor (C5i)–experienced (APPLY-PNH; NCT04558918) and C5i-naive (APPOINT-PNH; NCT04820530) patients with paroxysmal nocturnal hemoglobinuria (PNH). In the APPLY-PNH and APPOINT-PNH trials, changes in fatigue (Functional Assessment of Chronic Illness Therapy–Fatigue [FACIT-Fatigue]) and health-related quality of life (HRQOL; European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire [EORTC QLQ-C30]) from baseline to day 168 were evaluated. The proportion of patients achieving meaningful within-patient change (MWPC) on the FACIT-Fatigue and 4 EORTC QLQ-C30 subscales was evaluated using anchor-based thresholds, and correlations between FACIT-Fatigue scores, lactate dehydrogenase (LDH), and hemoglobin (Hb) levels were assessed. In APPLY-PNH (iptacopan, n = 62; C5i, n = 33), more patients in the iptacopan versus the C5i group reached the MWPC threshold for FACIT-Fatigue (51% vs 11%). More patients achieved MWPC on EORTC QLQ-C30 subscales in the iptacopan group (39%-49%) versus the C5i group (9%-20%). In APPOINT-PNH (N = 40), 56% achieved MWPC on the FACIT-Fatigue, and the proportion of patients who achieved MWPC on the EORTC QLQ-C30 ranged from 41% to 55%. In C5i-experienced patients, increased Hb levels correlated with improvement in FACIT-Fatigue scores (R = 0.48); in C5i-naive patients, increased Hb (R = 0.42) and decreased LDH (R = −0.53) (all P < .001) correlated with improved FACIT-Fatigue scores. C5i-experienced and -naive patients receiving iptacopan exhibited meaningful improvement in fatigue, HRQOL, and disease-related symptoms, which correlated with clinical improvement in hematologic markers of disease control.